Axenic Culture of Rice (KDML 105) - Surin Peyachoknagul; Pradit Pongtongkom; Paderm Ratisoontorn; Saowanee Suputtitada; Lertlak Ngernsiri; Punnee Rodrangboon (Agriculture and Natural Resources, 1994)
Callus from seeds of rice var. Khao Dawk Mali 105 was induced on the modified Murashige and Skoog (MS) agar medium (1962) supplemented with 15 percent coconut water, 1 g/l casein hydrolysate and various concentrations of 2,4-D, NAA and kinetin. The highest percentage of callus formation (62.50%) was obtained when cultured on the medium supplemented with 1 mg/l each of 2,4-D, NAA and kinetin. About 30 percent of these calli were regenerated to plantlets on the medium containing 2 mg/l kinetin. Seeds cultured on the modified MS agar medium supplemented with 15 percent coconut water and various concentrations of BAP and GA3 produced more than 20 shoots on the medium with 10 gm/l BAP. After transferring these shoots to the modified MS agar medium without growth regulators roots were induced and subsequently developed to plantlets. About 90 percent of these plantlets could survive after transplanting to the greenhouse.